Risk management and agency theory: Role of the put option in corporate bonds - Manish Tewari; Pradipkumar Ramanlal (Journal of Risk and Financial Management, 2022)
This study sets out a new methodology to exemplify, through a set of risk metrics called the Greeks, impact of a bond's structured provisions (e.g., call, put, and conversion options) on its risk characteristics and its propensity for agency conflicts. The methodology is assessed by applying it to a sample of 159 non-convertible bonds, with time-scheduled call and put provisions issued between 1977 and 2005. A structural contingent-claims valuation model is used to value the bonds and estimate the Greeks. The methodology is used to assess the impact of the call and put provisions on the bond's credit risk and interest-rate risk, as well as the provisions' ability to mitigate the agency conflict associated with over-investment, under-investment, asset-substitution, and information asymmetry about the firm's true risk among stakeholders. The main findings of this study are that the put option plays a key role in reducing credit risk, mitigating agency conflict, and protecting against volatility shocks; conversely, the call option plays a key role in reducing interest-rate risk. The methodology is sufficiently general to apply to bonds and preferred stock with any set of structured provisions.
Keywords: 330; corporate financing; asset pricing; callable putable bonds; risk measures; information asymmetry; agency theory